Chlamydia trachomatis Alters Iron-Regulatory Protein-1 Binding Capacity and Modulates Cellular Iron Homeostasis in HeLa-229 Cells. (16th August 2009) - Vardhan, Harsh; Bhengraj, Apurb R.; Jha, Rajneesh; Singh Mittal, Aruna
Abstract : Chlamydia trachomatis (CT) is the leading cause of diseases related to reproductive health and iron plays important role in chlamydial pathogenesis. Iron homeostasis in chlamydia-infected cells is not clear thus far. This study shows that expression of the transferrin receptor (TfR) is downregulated, whereas expression of the ferritin heavy chain is upregulated in CT-infected HeLa-229 cells. Expression of iron-regulatory protein (IRP)-1 predominates over IRP-2 in infected cells. In infected cells, attenuated binding activity of IRP-iron responsive elements (IREs) is observed using the electrophoretic mobility-shift assay. These results suggest that iron homeostasis is modulated in CT-infected HeLa cells at the interface of acquisition and commensal use of iron.